Green growth, technology and innovation - Dutz, Mark A.; Sharma, Siddharth (2012)
The paper explores existing patterns of green innovation and presents an overview of green innovation policies for developing countries. The key findings from the empirical analysis are: (1) frontier green innovations are concentrated in high-income countries, few in developing countries but growing; (2) the most technologically-sophisticated developing countries are emerging as significant innovators but limited to a few technology fields; (3) there is very little South-South collaboration; (4) there is potential for expanding green production and trade; and (5) there has been little base-of-pyramid green innovation to meet the needs of poor consumers, and it is too early to draw conclusions about its scalability. To promote green innovation, technology and environmental policies work best in tandem, focusing on three complementary areas: (1) to promote frontier innovation, it is advisable to limit local technology-push support to countries with sufficient technological capabilities -- but there is also a need to provide global technology-push support for base-of-pyramid and neglected technologies including through a pool of long-term, stable funds supported by demand-pull mechanisms such as prizes; (2) to promote catch-up innovation, it is essential both to facilitate technology access and to stimulate technology absorption by firms -- with critical roles played by international trade and foreign direct investment, with firm demand spurred by public procurement, regulations and standards; and (3) to develop absorptive capacity, there is a need to strengthen skills and to improve the prevailing business environment for innovation -- to foster increased experimentation, global learning, and talent attraction and retention. There is still considerable progress to be made in ranking green innovation policies as most appropriate for different developing country contexts -- based on more impact evaluation studies of innovation policies targeted at green technologies.